Feasibility and Surgical Effect of Annulus Sparing in Consecutive Patients with Tetralogy of Fallot: A Retrospective Cohort Study. Issue 4 (27th September 2022) - Lv, Lizhi; Liu, Jinyang; Jiang, Xianchao; Liu, Yang; Tian, Yanjin; Cao, Hong; Liu, Zhimin; Wang, Qiang
Abstract : Objective: Annulus-sparing (AS) repair for tetralogy of Fallot (TOF) with a dysplastic pulmonary valve annulus (PVA) is a challenging procedure and is controversial. This study aimed to assess the feasibility and surgical effect of AS repair versus transannular patch enlargement (TAPE) repair, especially in individuals with dysplastic pulmonary valves. Methods: This retrospective cohort study included 375 pediatric patients with a primary diagnosis of TOF in the Center for Pediatric Cardiac Surgery of Fuwai hospital from January 2014 to June 2017. Among them, 60 consecutive and nonselective patients underwent 1-stage repair of TOF with aggressive PVA-preserving strategies performed by a single surgeon were enrolled in AS cohort. In AS cohort, patients were divided into AS, PVA z-score ≥−2 group (33 patients) and AS, PVA z-score <−2 group (27 patients). During the same period, 315 patients underwent TAPE repair by other surgeons were enrolled as TAPE cohort, of these, 87 patients with PVA z-score ≥−2 were excluded. From the 228 patients in the TAPE group, 27 cases were selected as TAPE, PVA z-score <−2 group according to the propensity score and 1:1 ratio with AS, PVA z-score <−2 group. The primary outcome was a composite of reintervention, significant pulmonary regurgitation, and significant annular peak gradient (APG). Kaplan-Meier curve was plotted to show the survival rate of severe pulmonary regurgitation. Results: One death occurred after the TAPE operation in TAPE group, and 1 patient in the AS z ≥−2 group needed reintervention with a balloon. After a median follow-up of (30.3 ± 11.6) months, compared with AS z ≥−2 group, there was no difference in the technical performance score for severe pulmonary stenosis (APGs > 20 mmHg) in the AS z <−2 group. Compared with TAPE, AS repair was often accompanied by a postoperative APGs over 20 mmHg ( P = 0.001). More patients underwent TAPE suffered from moderate or severe pulmonary regurgitation than those who received AS repair (20 (74.1%) vs. 7 (26.0%), P < 0.001). AS repair was associated with a shorter duration of mechanical ventilation (20 vs. 29 hours, P = 0.039), faster discharge from the intensive care unit (2.0 vs. 4.0 days, P = 0.022) and shorter postoperative hospitalization (8.0 vs. 11.0 days, P = 0.008) compared with TAPE. Conclusions: APG demonstrated an upward trend in the TAPE group and a downtrend in the AS group after discharge from hospital. AS repair had an acceptable surgical effect in TOF patients, even in those with a dysplastic PVA. A higher APG remained upon hospital discharge in dysplastic patients with AS, but a downward trend was observed over time.